2009
DOI: 10.2752/175303709x457595
|View full text |Cite
|
Sign up to set email alerts
|

Relations among Need for Power, Affect and Attitudes toward Animal Cruelty

Abstract: Previous research has investigated the relationship betv*/een empathy with humans and attitudes toward animais, Deveioping a better understanding of this reiationship, as weli as other reiated variables, may assist in the prevention ot antisocial behavior. The purpose of the current study was to investigate the reiationship between sensitivity toward the mistreatment of animais, negative affect, and need for power. Participants were 198 introductory Psychoiogy students, 98 (49.5%) women and 100 (50.5%) men. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The offending behavior literature shows that members of the community who endorse offence-supportive attitudes (e.g., self-reported rape proclivity) share similar (if not the same) attitudes and beliefs as apprehended offenders (Bohner et al, 1998;Malamuth & Check, 1980). Of the 10 studies examining the characteristics of animal abusers and/or people who endorse attitudes supportive of animal abuse, two (20.0%) studies identified animal abusers from criminal records (i.e., participants had a criminal conviction of animal cruelty - Arluke et al, 1999;Green, 2002), two (20.0%) studies used self-report items/questionnaires to assess perpetration of animal abuse (Febres et al, 2012;Febres et al, 2014), three (30.0%) studies only assessed attitudes toward the treatment of animals (Alleyne, Tilston, Parfitt, & Butcher, 2015;Oleson & Henry, 2009;Raupp, 1999), and the remaining studies (n = 7, 35.0%) assessed both prior perpetration of animal abuse and attitudes toward the treatment of animals (DeViney et al, 1983;Erlanger & Tsytsarev, 2012;Gupta, 2008).…”
Section: Measures Of Animal Abuse Behavior and Offence-supportive Attmentioning
confidence: 99%
See 2 more Smart Citations
“…The offending behavior literature shows that members of the community who endorse offence-supportive attitudes (e.g., self-reported rape proclivity) share similar (if not the same) attitudes and beliefs as apprehended offenders (Bohner et al, 1998;Malamuth & Check, 1980). Of the 10 studies examining the characteristics of animal abusers and/or people who endorse attitudes supportive of animal abuse, two (20.0%) studies identified animal abusers from criminal records (i.e., participants had a criminal conviction of animal cruelty - Arluke et al, 1999;Green, 2002), two (20.0%) studies used self-report items/questionnaires to assess perpetration of animal abuse (Febres et al, 2012;Febres et al, 2014), three (30.0%) studies only assessed attitudes toward the treatment of animals (Alleyne, Tilston, Parfitt, & Butcher, 2015;Oleson & Henry, 2009;Raupp, 1999), and the remaining studies (n = 7, 35.0%) assessed both prior perpetration of animal abuse and attitudes toward the treatment of animals (DeViney et al, 1983;Erlanger & Tsytsarev, 2012;Gupta, 2008).…”
Section: Measures Of Animal Abuse Behavior and Offence-supportive Attmentioning
confidence: 99%
“…One study developed items asking participants to self-8 report engagement in animal abuse behavior (DeViney et al, 1983). Six of the studies reviewed used established scales/measures to assess animal abuse perpetration and offence-supportive attitudes (Alleyne et al, 2015;Erlanger & Tsytsarev, 2012;Febres et al, 2012;Febres et al, 2014;Gupta, 2008;Oleson & Henry, 2009;Raupp, 1999). To assess animal abuse perpetration, three scales were used: the Aggression Toward Animals Scale (Gupta & Beach, 2001), the adapted Boat (1999) Inventory on Animal-Related Experiences (Flynn, 1999), and the adapted version of Flynn's (1999) Experiences with Animals self-report survey (Henry & Sanders, 2007).…”
Section: Measures Of Animal Abuse Behavior and Offence-supportive Attmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, our findings echo the commonly observed fact that males are more aggressive and more adventurous than females (Lips, 2008); clearly this can lead them to be more likely to perpetuate as well as explore the consequences of harmful acts on animals. As pointed out by Oleson and Henry (2009), male hostility and the need for power are related to animal cruelty. The data also suggested then when children harmed animals, interpersonal violence was common (not associated with the CAI), but the presence of guns, domestic violence and violence towards animals were associated with higher CAI scores, suggesting that these activities may have some bearing as to how children interact with animals.…”
Section: Gender and Harm Of Animalsmentioning
confidence: 99%
“…Animal welfare researchers are exploring potential correlates of animal abuse with the aim of identifying risk factors and prevention strategies for such behaviour [17,18]. One such correlate may be attitude towards animals.…”
Section: Introductionmentioning
confidence: 99%